1946
DOI: 10.1111/j.1744-7348.1946.tb06268.x
|View full text |Cite
|
Sign up to set email alerts
|

Some causes of chlorosis and necrosis of sugar‐beet foliage

Abstract: The symptoms and characteristics of two virus and one fungus disease and four nutritional disorders of sugar beet which cause chlorosis and necrosis of the foliage are described. The causes of the diseases and methods of distinguishing between them have been investigated by analytical, pathological and field experimental methods.Experiments in which diagnosis was confirmed by serological and spectrochemical methods show that the two often easily confused diseases, sugar‐beet yellows virus and magnesium deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1949
1949
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Manganese is essential for photosynthesis and is involved in carbon and nitrogen metabolism within plant tissue (Gregory 1971;Terry & Ulhrich 1975). Symptoms of manganese deficiency in sugarbeet in the UK were first described more than 50 years ago by Da vies (1939) and later by Hale et al (1946). Chlorotic symptoms can develop by early May and, unless treated, arc followed by curling of leaf margins and then by necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese is essential for photosynthesis and is involved in carbon and nitrogen metabolism within plant tissue (Gregory 1971;Terry & Ulhrich 1975). Symptoms of manganese deficiency in sugarbeet in the UK were first described more than 50 years ago by Da vies (1939) and later by Hale et al (1946). Chlorotic symptoms can develop by early May and, unless treated, arc followed by curling of leaf margins and then by necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of chlorosis in grass seedlings in the untreated and low-Se treatments is unlikely associated with a lack of nutrients in the tailing material (Hale et al 1946). The tailing materials were collected from under a thick humus layer created by decades-old spruce forest which indicates there were sufficient nutrients to support the forest despite the toxic nature of the tailings (it is of note that the understory was observed to be quite sparse in this area relative to neighbouring forests away from the tailings).…”
Section: Do Sodium Selenite Additions Change the Toxicity Of Hg And Amentioning
confidence: 92%
“…Chlorosis, a condition in which plant leaves produce insufficient chlorophyll, can be in response to insufficient nutrients or toxic conditions (Hale et al 1946;Shaibur et al 2006). The number of grass shoots affected by chlorosis decreased significantly with increased [Se] treatments, with no chlorosis observed for grass seedlings in the 15 mg Se/kg treatment (Table 2 Week Despite the lack of significance in earthworm mortality with soil and plant parameters, it is worth noting that only the earthworms in the untreated 0 mg Se/kg tailing material replicates had observable surface pathologies.…”
Section: Plant Growth Testmentioning
confidence: 99%
“…There is no need to discuss here at length the use of plant analysis for the diagnosis of mineral deficiency, for the subject has been adequately reviewed elsewhere (Goodall & Gregory, 1947 Hale, Watson & Hull (1946) found that the leaves of sugar-beet plants showing symptoms of manganese deficiency almost always had a manganese content less than 25-30 p.p.m. Marsh & Powers (1945) considered IOO p.p.m.…”
Section: Studies In the Diagnosis Of Mineral Dejciencymentioning
confidence: 99%